ChemInform Abstract: Novel One‐, Two‐, and Three‐Dimensional Selenidostannates Templated by Iron(II) Complex Cation. Issue 42 (14th October 2014) - Tang, Chunying; Wang, Fang; Lu, Jialin; Jia, Dingxian; Jiang, Wenqing; Zhang, Yong
Abstract The new selenidostannates (IV) and (V) are hydrothermally synthesized in the presence or absence of KSCN, respectively.